Leukocyte telomere length is not affected by long-term occupational exposure to nano metal oxides - Hubacek, Jaroslav A; Pelclova, Daniela; Dlouha, Dana; Mikuska, Pavel; Dvorackova, Stepanka; Vlckova, Stepanka; Fenclova, Zdenka; Ondracek, Jakub; Kostejn, Martin; Schwarz, Jaroslav; Popov, Alex; Krumal, Kamil; et al. (Industrial health, 2019)
The aim of this study was to ascertain whether long-term occupational exposure to nanoparticles would affect relative leukocyte telomere length (LrTL). We analysed occupational exposure to size-resolved aerosol particles, with special emphasis on nanoparticles at two workshops: i/ the production of nanocomposites containing metal oxides; ii/ laboratory to test experimental exposure of nano-CuO to rodents. Thirty five exposed researchers (age 39.5 ± 12.6 yr; exposure duration 6.0 ± 3.7 yr) and 43 controls (40.4 ± 10.5 yr) were examined. LrTL did not significantly (p=0.14) differ between the exposed researchers (0.92 ± 0.13) and controls (0.86 ± 0.15). In addition, no significant correlation (r=-0.22, p=0.22) was detected between the duration of occupational exposure and LrTL. The results remained non-significant after multiple adjustments for age, sex and smoking status. Our pilot results suggest that relative leukocyte telomere length is not affected by occupational exposure to nanoparticles.
Keywords: Male; lidé středního věku; Metal nanoparticles; Leukocytes; Occupational Exposure; Telomere length; pracovní expozice; Humans; Air Pollutants, Occupational; Middle Aged; Czech Republic; Česká republika; mužské pohlaví; oxidy; Female; Oxides; látky znečišťující vzduch v pracovním prostředí; ženské pohlaví; Research Personnel; Adult; kovové nanočástice; Metal Nanoparticles; Follow-up; Telomere Shortening; zkracování telomer; dospělí; lidé; výzkumní pracovníci; leukocyty